Hubungan Sikap Dan Asupan Karbohidrat Terhadap Kadar Glukosa Darah Pada Pasien Rawat Jalan Diabetes Mellitus Tipe II Di RSUD Dr. Moewardi - Ingrid, Seliana, Elida Soviana, S.Gz., M.Gizi, Dyah Widowati, SKM (2015)
Background: uncontrolled diabetes mellitus will to complication that arise such as stoke, hypertension, and heart disease. Blood glucose levels can be controlles either by the attitude of meal planning and carbohydrat inteke. Objektive : to know the relationship of attitude ang carbohydrate intake on blood glucose levels in patients with diabetes mellitus. Methods: this study was on observasional with cress sectional approach. Data use attitude questionnaires, the data intake og carhohydrates using 4x24 recall hours are not sequential and for fasting blood glucose levels by looking at the laboratory. Data analysis using persont prodact moment. Results: the pattient's attitude meal planning is goos enough for (95,5%), carbohydrate intake is sufficient (99,98%)63,6% of the samples had a moderate sttitude meal planning, 63,6% og the samples had a carbohydrate intake of less and 74,5% of the samples have blood glucose levels that are not normal. Based on the results of persont prodact moment, there is no relationship attitude and food intake of carbohydrate on blood glucose levels. Conclusion : there is no relationship attitude about blood glucose levels, there was no association of carbohydrate intake on blood glucose levels. Advice: for patients diabetes mellitus, expected to change attitude of planning to eat the kinds of food fan anything nestling containsimple carbohydrate. For nutritional installation, is expected to improve sevise optimally, especially in educating patients about the management of diabetes mellitus.